Multimedia development of basic technique learning for posture and step patterns based on website oriented to Project-Based Learning - Awalinda Safitri; I Gede Suwiwa; I Komang Sukarata Adnyana (Sriwijaya Journal of Sport, 2025)
Research Problems: Mastery of the basic techniques of the ready stance and stepping patterns in martial arts remains a challenge for students due to the limited availability of interactive and accessible learning media. Therefore, it is necessary to develop a web-based multimedia learning tool that integrates a Project-Based Learning approach to enhance students' understanding and skills independently and contextually. Research Objectives: This study aims to develop a web-based multimedia learning product focused on basic techniques of the ready stance and stepping patterns, oriented toward Project-Based Learning, for the course "Theory and Practice of Pencak Silat Instruction. Methods: This research adopts the Borg and Gall development model, which consists of 10 stages: (1) preliminary research and data collection, (2) planning, (3) developing a draft product, (4) initial field testing, (5) revision of test results, (6) main product field testing, (7) product revision, (8) large-scale field testing/feasibility testing, (9) final product revision, and (10) dissemination and implementation. However, this study is limited to stage 9 due to time and financial constraints. The research design includes expert validation, product testing, and practicality testing, involving lecturers and students of the Physical Education, Health, and Recreation Program at the Faculty of Sport and Health, Ganesha University of Education. Data were collected through questionnaires and analysed using both qualitative descriptive and quantitative descriptive methods. Results: The results showed that content expert validation scored 95% (excellent), media expert validation scored 96% (excellent), design expert validation scored 90% (excellent), individual trials scored 96% (excellent), small group trials scored 94.5% (excellent), large group trials scored 94.3% (excellent), and practicality testing scored 92.8% (excellent). Conclusion: It can be concluded that the developed multimedia learning tool is feasible and effective as a learning medium for Pencak Silat, specifically for the basic techniques of the ready stance and stepping patterns.